INFORMATION RISK MANAGEMENT a practitioner's guide. - SUTTON, DAVID (BCS, THE CHARTERED INSTIT, 2021)
Information risk management (IRM) is about identifying, assessing, prioritising and treating risks to keep information secure and available. This book provides practical guidance to the principles and development of a strategic approach to an IRM programme. The only textbook for the BCS Practitioner Certificate in Information Risk Management.
Keywords: Information technology -- Management.; Risk management.; elektronické knihy; electronic books